2020
DOI: 10.1016/j.nedt.2019.104234
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the influences on under-representation of male pre-registration nursing students

Abstract: , Twitter: @JasTay10r Funding: Commissioned and funded by NHS Education Scotland (NES) Conflict of Interest: None declared Ethical Approval: Ethical approval was gained from each of the participating academic institutions for all locally conducted phases of data collection (Ethics numbers: SREC 2017010; SREC 2017034; STAFF003; STAFF009; SERP ref 10-04). Approval for the national school teacher survey was gained from one institution (SREC 2018004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…Similarities and differences were found among the male nurses in Mainland China and Macau regarding joining and remaining in nursing. Our study supports previous findings that motivations to induce males into nursing are related to social attitudes toward male nurses and the economic prospects of being nurses [21,22]. We found that male nurses in Macau and the Mainland were not widely accepted by the public, particularly in the Mainland.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarities and differences were found among the male nurses in Mainland China and Macau regarding joining and remaining in nursing. Our study supports previous findings that motivations to induce males into nursing are related to social attitudes toward male nurses and the economic prospects of being nurses [21,22]. We found that male nurses in Macau and the Mainland were not widely accepted by the public, particularly in the Mainland.…”
Section: Discussionsupporting
confidence: 89%
“…The males of both sides, particularly the Mainland males, entered nursing out of economic consideration. Both sides revealed the financial constraints of male nurses' families, echoing other studies which suggest that male nurses might be from families of lowmiddle to low economic conditions [21,25]. Driven into nursing almost exclusively out of economic benefits, male nurses in China often face a dilemma--while nursing can secure a stable urban life for men coming from the hardships of the countryside and small towns, these men are increasingly vulnerable to leaving nursing when exposed to more job opportunities.…”
Section: Discussionmentioning
confidence: 83%
“…Traditionally, the caring and nurturing aspect of nursing has been associated with women and femininity, which is reinforced by the continued low number of men in nursing 1 . While the number of males in nursing is increasing 1,2 males remain a minority worldwide accounting for approximately 10% of the nursing workforce 3‐6 . While other professions, such as medicine and engineering have made advances in addressing gender inequities, nursing has been unsuccessful in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature, several common themes emerge as factors that negatively affect the recruitment of men into nursing: perception of nursing, public perception of men in nursing, and the influence of significant others 4,7 . The stereotypical belief that nursing is a female profession, not suitable for men, continues to influence the decisions of men to decline nursing as a career choice 2,5 . Career advisors may direct higher achieving students away from nursing, possibly perpetuating a negative perception of nursing in the minds of the students 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation